Modulation of BAG3 expression in human normal urothelial cells by Diuron. Issue 4 (18th August 2020) - Eletto, Daniela; Reppucci, Francesca; Ronga, Agostino; Altieri, Vincenzo; Brongo, Sergio; Martinelli, Rosanna; De Marco, Margot; Marzullo, Liberato
Abstract: Diuron [3‐(3, 4‐dichlorophenyl)‐1, 1‐dimethylurea] is a substituted urea herbicide, carcinogenic for the rat urinary bladder. It has been hypothesized that Diuron cytotoxicity, resulting in regenerative proliferation, leads to urothelial hyperplasia and, finally, to bladder tumors, but molecular mechanisms of carcinogenesis have not still fully investigated. Here, we report the results of a study aimed at verifying the involvement of BAG3, an intracellular protein expressed in several tumors, in the Diuron‐induced carcinogenesis. For this purpose, we analyzed the effect of Diuron on human primary urothelial cells and on human dermal fibroblasts. We found that while high concentrations of Diuron have a cytotoxic effect in human primary urothelial cells, in the same cells, noncytotoxic concentrations of the herbicide induce BAG3 expression. These findings show that BAG3 is a molecular target of Diuron and unravel the possible involvement of BAG3 protein in bladder carcinogenesis induced by the herbicide. In addition, these results suggest that BAG3 might be a potential early biomarker of damage induced by chronic exposure to Diuron. Abstract : High concentrations of Diuron have a cytotoxic effect in human primary urothelial cells. In some human primary cells, BAG3 is upregulated by noncytotoxic concentrations of Diuron and might be a potential early biomarker of damage induced by chronic exposure to the herbicide.